A Cryptography Algorithm Using Laplace Transformation - Tharaka Ruwan, Samarasingha Mudiyanselage; Ekanayake, Ekanayake Mudiyanselage Uthpala Senarath Bandara (International Journal of Integrative Sciences, 2024)
There are numerous uses for the Laplace Transform (LT) across various fields. The literature attests to the fact that various methods have been developed in the past to solve cryptography using LT. In contrast to some methods, like those found in Stanoyevitch's Introduction to Cryptography with Mathematical Foundations and Computer Implementations, Barr's Invitation to Cryptography, Blakley's Twenty Years of Cryptography in the Open Literature, and others, this study presents a new cryptographic system that uses the Laplace transform and Taylor series expansions to increase security and effectiveness. A valuable tool in the field of secure communication, the proposed scheme's two-part encryption strategy and key-based approach offer strong protection against unauthorized access. It is also computationally difficult for adversaries to decipher the entire message without both keys, thanks to the extra layer of security added by the two-part encryption technique. This feature works especially well in situations where the message is very long. In comparison to the well-known algorithms that are currently in the literature, the algorithmic approach that this study proposes is less complex. We use a case study at the end to demonstrate the suggested approach